Satisfaction of Patients, Coronary Arteries in Related to Nursing and Medical Care - Al-Shammary, yass; AL-Gersha, Khalida (Iraqi National Journal of Nursing Specialties, 2014)
Objectives of the study: The study aims to assess satisfy of the coronary artery patients for the care product fromthe nurse and physician and to find out the relationship between patient satisfaction with the social and theclinical characteristics of the patients.Methodology: A descriptive design study conducted using the evaluation approach for the duration of June 3rd2012 to January 31, 2013. Non-probability sample of (60) patients who were visiting or admitted (inpatient oroutpatient) to the teaching hospital in Baquba with the diagnosis of coronary artery disease. A questionnaire havebeen built and develop by the researcher based on review of literature and previous research, the form included of(3) parts: Part I demographic characteristics such as age, gender, education level, marital status, occupation,monthly income, the second part of clinical data and the third part assessing the satisfaction of patient about thequality of the physicians care, the quality of nurses care and satisfaction in general.(12).Reliability was identifiedthrough the use of (test and retest).The validity was identified by offering experts with competence. The data wereanalyzed using descriptive statistics and inferential statistical analysis approachResults: The results of the study showed that the highest percentage (53.3%) was males under age groups (60-69)and (36.7%) of the sample were unable to read and write. The study showed that (75.0%) of the sample weremarried, (41.7%) of the sample were female and housewife (61.7%) of the respondents live in the city, and (91.7%)of the sample had one source of income and (61.7%) of the sample had not sufficiently a monthly income. Theresults of the study shows that the patients with coronary artery disease were not satisfy with the care providedby the nurse, the physician and general care in most of the sub domains.Recommendations: The study recommended there is a need to writing standard education program for the nurseand the physician in cardiac care unit to improve the care provided to the patient and establishment cardiac centerrehabilitation in all governorate to produce the service to the patient